15-minute Spanish : learn in just 12 weeks - Bremón, Ana (DK, 2023)
"DK's 15 Minute Spanish is the perfect course for busy people who want to learn Spanish fast. The 12 themed chapters are broken down into easy-to-follow 15-minute daily lessons spanning a range of practical themes, including: leisure, business, food and drink, travel, and shopping. Each lesson combines vocabulary and grammar essentials with attractive full-color images, making it quick, easy, and fun to learn new Spanish vocabulary. There is no writing or homework--you simply use the cover flaps to hide the answers to exercises and test yourself as you learn. Each chapter ends with a review module, so you can track your progress and identify areas where you need further practice"--